Green hydrogen futures in LMICs: Opportunities for fertilizer and steel production in Kenya - Pietro Lubello; Joshua Oduor; Anne Nganga; Martin Mutembei; Francis Njoka; Michelle Akute; Kihara Mungai; Steve Pye (iScience)
Summary: Green hydrogen is often presented as a promising driver of green industrial development in low- and lower-middle-income countries (LMICs), with national strategies balancing local applications promoting sustainable development alongside export opportunities. Country-level energy system models can help identify no-regret options by comparing the costs of local green alternatives to market prices, reducing the risk of uneconomic investments that could hinder local development. We present an open-source capacity expansion model for Kenya to explore the role of green hydrogen in local fertilizer and steel industries under various market and technology development scenarios. With abundant renewable energy resources, we estimate that Kenya could produce hydrogen at 2.7–3.7 USD/kg, making local options competitive from the second half of the 2030s, provided high market prices and substantial additional investments in the development of the sectors. The Kenya case study offers valuable insights for other LMICs as they design and implement their national strategies.